1995
DOI: 10.1080/09537289508930284
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of some priority dispatching rules under different shop loads

Abstract: Priority dispatching rules and shop load affect jobshop performance. This paper evaluates ten different priority dispatching rules with respect to six different performance criteria under light, medium and heavy shop loads. Simulation was used as a tool to determine the rankings of the dispatching rules for a given shop load and performance criteria. A comparative study was conducted to investigate the performance of these rules. Two rules, 'shortest processing time' and 'least work remaining'. performed well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…The middle column of Figure 1 shows the comparative priority rule rankings used to solve the traditional as well as the flexible job shop problem for each of the five objective functions. The graphs show that the relative performance of the priority rules to solve the problems under the mean flow time, mean tardiness and proportion of tardy jobs objectives does not differ much from their performance on the classical job shop scheduling problem, which partly confirms the conjecture of Waikar et al (1995). However, the best performing rule for the traditional job shop problem is not always the best one for its flexible variant.…”
Section: Flexible Job Shop Problemsupporting
confidence: 65%
See 4 more Smart Citations
“…The middle column of Figure 1 shows the comparative priority rule rankings used to solve the traditional as well as the flexible job shop problem for each of the five objective functions. The graphs show that the relative performance of the priority rules to solve the problems under the mean flow time, mean tardiness and proportion of tardy jobs objectives does not differ much from their performance on the classical job shop scheduling problem, which partly confirms the conjecture of Waikar et al (1995). However, the best performing rule for the traditional job shop problem is not always the best one for its flexible variant.…”
Section: Flexible Job Shop Problemsupporting
confidence: 65%
“…This block is inspired by the remarks of Dominic et al (2004) who concluded that 9 The results of the comparative study are displayed in Table 2 for each of the five objective functions. It is worth noting the similar comparative studies has been made by other authors, such as Waikar et al (1995), Holthaus and Rajendran (1997), Rajendran and Holthaus (1999), Holthaus and Rajendran (2000), Jayamohan and Rajendran (2000), Jayamohan and Rajendran (2004), Dominic et al (2004) and Chiang and Fu (2007), but with a slightly different focus or limited scope compared to our full comparison on the five objective functions. The results can be briefly summarized per objective function along the following paragraphs.…”
Section: Comparative Resultsmentioning
confidence: 83%
See 3 more Smart Citations